2020
DOI: 10.21203/rs.3.rs-34085/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serum metabolomic profile of symptomatic and asymptomatic SARS-CoV-2 infected patients 

Abstract: Background: One of the most challenging aspects related to Covid-19 is to establish which are the characteristics that may explain clinical variability among patients. To achieve this objective, we compared serum metabolomic profiles of asymptomatic SARS-CoV-2 carriers to patients affected by mild and severe symptoms.Methods: All subjects underwent quantitative assays for anti-SARS-CoV-2 antibody detection. Serum samples for metabolomic analysis were obtained from 109 healthy controls; 15 seroconverted, asympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
(57 reference statements)
3
3
0
Order By: Relevance
“…Changes in primarily polar metabolites among COVID-19 patient cohorts from China, Italy, and France have been reported. [9][10][11][12] In agreement with those studies, we observed a dysregulation of amino acid pools, interruption of the glucose to lactate balance, and dysregulation of nucleotide catabolic products such as xanthine, hypoxanthine, and urate (Sup. Fig.…”
Section: Main Textsupporting
confidence: 91%
See 1 more Smart Citation
“…Changes in primarily polar metabolites among COVID-19 patient cohorts from China, Italy, and France have been reported. [9][10][11][12] In agreement with those studies, we observed a dysregulation of amino acid pools, interruption of the glucose to lactate balance, and dysregulation of nucleotide catabolic products such as xanthine, hypoxanthine, and urate (Sup. Fig.…”
Section: Main Textsupporting
confidence: 91%
“…[4][5][6] While several studies have examined the systemic metabolic correlates of COVID-19, a well resolved interrogation of the lipidomic changes in COVID-19 severity has not been pursued. [9][10][11][12] To measure lipidomic changes in COVID-19 and gain mechanistic insights into how these changes may drive disease severity, we used serum draws from 19 healthy patients (healthy), 18 COVID-19 patients who did not require ICU admission (moderate) and 20 patients that required ICU admission (severe). The demographics, preexisting conditions, and treatment details of these patients are indicated in Table 1.…”
Section: Main Textmentioning
confidence: 99%
“…Our results are in line with other COVID-19 metabolomics analyses, with emphasis on the relevance of amino acid catabolism during hypoxic conditions 7 9 . Interestingly, these metabolic signatures may have implications on the appearance of adverse effects due to SARS-CoV-2 infection, such as diabetes and neurological disabilities.…”
Section: Introductionsupporting
confidence: 91%
“…Our results are in line with other COVID-19 metabolomics analyses, with emphasis on the relevance of amino acid catabolism during hypoxic conditions [7][8][9] . Interestingly, these metabolic signatures may have implications on the appearance of adverse effects due to SARS-CoV-2 infection, such as diabetes and neurological disabilities.…”
Section: Introductionsupporting
confidence: 91%